Сomparative analysis of the legal consequences of an expiry of the period for imposition of administrative penalties in ukrainian and russian legislation - Токарєва, Ксенія Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article is devoted to the scientific analysis of the legal consequences of the expiration of the period for the imposition of administrative penalties in ukrainian and russian legislation. There is provided a brief theoretical overview of the definitions, are defined the main law enforcement problems of expiration of the imposition of administrative penalties, is given the analysis of judicial practice.